Assessment of heavy metals in foods around the industrial areas: health hazard inference in Bangladesh. Issue 3 (17th February 2020) - Islam, Md. Saiful; Proshad, Ram; Asadul Haque, Mohammad; Hoque, Md. Fazlul; Hossin, Md. Shahin; Islam Sarker, Md. Nazirul
Abstract: This research was conducted to assess the concentration of six heavy metals ie, chromium (Cr), nickel (Ni), copper (Cu), arsenic (As), cadmium (Cd) and lead (Pb) in different foods associated with health hazard inference in Bangladesh. The range of Cr, Ni, Cu, As, Cd and Pb in food samples were 0.45–47.7, 0.22–38.6, 0.43–47.4, 0.72–6.05, 0.001–6.70 and 0.21–35.9 mg/kg, respectively. The estimated daily intake values of all the metals except Cu were higher than the maximum tolerable daily intake. The target hazard quotients of all metals were higher than 1 through consumption of cereal and vegetables, indicating significant health risks to both adult and children. The total carcinogenic risk (CR) of As (9.84E–01) was higher the threshold level (1.0E–06) and 9.84E–01 for Pb clearly revealed that consumption of these food items definitely poses cancer risks to the Bangladeshi population.